Combinatorial Price Offer for a Wind Turbine with Flexible Load Considering the Uncertainty to Increase the Benefit of Wind Turbine - Behnam Sobhani; Sadegh Afzal (Advances in Engineering and Intelligence Systems)
Wind energy is one of the most important renewable energies in the present and future. However, one of the significant challenges is offering the amount of generation and generation price in the next-day market because, on the one hand, this energy has nonlinear behavior, and on the other hand, any imbalance between forecast and generation results in the generation unit being fined. In this paper, a method is presented to propose wind turbine generation by increasing the forecast accuracy and combination with flexible load and uncertainties. This increases the revenue of the wind generator companies and consumers and guarantees the connection of wind generators. In fact, in this paper, the agreed price between the wind and load is flexible so this agreed performance will be beneficial to both wind generation and the elastic load. In this modeling, first, the system equations in the market are written and merged. To increase the revenue, the uncertainties are considered, and it is shown that their effect can change the gain in wind turbine and load. The price and wind prediction will be conducted using one of the previous methods, and the primary purpose here is to increase the system revenue. To sum up, this paper introduces the integrated offering strategy model for wind turbines, and the demand response to the support of wind turbines in the power market is proposed. This strategy aims to increase renewable generations and demand profits in the day-ahead market. In this paper, the suggestions include the integrated offering of power, uncertainty modeling, using the neural-fuzzy model for predictions, flexible loads, etc. are proposed to achieve the optimal profits. Modeling is done using the MATLAB application to calculate Spain's wind and price information in Spain, and the performance output results are demonstrated thoroughly.